Sociocultural competence-oriented curriculum for engineering education in Russia; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Galanina E. V. Ekaterina Vladimirovna (2016, 2016)
Title screen